The quality of educators - Croatian early and preschool education and schooling system quality factor - Križman Pavlović, Danijela; Bušelić, Marija; Gal, Silvana (Oeconomica Jadertina, 2020)
Participation in early and preschool education and schooling (EPES) brings numerous potential benefits to the individual, but also to society as a whole. In the last decade, the demand for EPES services has increased (OECD countries). The main challenges that the education policy makers in European countries are currently facing are the access and quality of EPES services. The quality of educators is one of the most important factors in the quality of EPES. Therefore, the authors conducted a primary and secondary research on the quality of educators as a significant factor in the quality of the Croatian EPES system. The quality of educators was measured using structural quality indicators at two levels of the system (international/national level and kindergarten level). Among other things, the research resulted in recommendations for improving the quality of educators, from which all stakeholders in the Croatian EPES can benefit.